2021
DOI: 10.3390/healthcare9060666
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study between 18F-FDG PET/CT and Conventional Imaging in the Evaluation of Progressive Disease and Recurrence in Ovarian Carcinoma

Abstract: The aim of this study is to compare the efficiency of conventional imaging and 18F-FDG PET-CT in detecting progressive disease and recurrences over a period of one year (2018), in the case of ovarian cancer, and also to assess the importance of 18F-FDG PET/CT in changing the course of the treatment for these patients. This study included 29 patients diagnosed in various stages with ovarian carcinoma, most of them of epithelial origin. All patients were evaluated throughout their treatment using 18F-FDG PET/CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Another point is that PET-CT is relatively safe. Although the radionuclides required for its examination are radioactive, the amount of ethical radionuclides required is very small, and the half-life of the radionuclides used is very short [ 19 , 20 ]. The radionuclides will have a limited retention time in the subject's body due to the combined action of biological metabolism and physical attenuation, and will have no harmful effects on the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Another point is that PET-CT is relatively safe. Although the radionuclides required for its examination are radioactive, the amount of ethical radionuclides required is very small, and the half-life of the radionuclides used is very short [ 19 , 20 ]. The radionuclides will have a limited retention time in the subject's body due to the combined action of biological metabolism and physical attenuation, and will have no harmful effects on the human body.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the higher e ciency of 18FDG PET/CT than CT and MRI in identifying recurrent OC, it can also identify recurrences of OC approximately six months before CT (23).Consequently, 18FDG PET/CT can be used effectively for surveillance of treated OC patients, particularly when conventional imaging methods had negative results but there is an increase in the CA-125 level or the clinical examination may indicate recurrence or progression (24).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, 18 F-FDG PET/CT imaging is superior to other imaging examinations in diagnosing ovarian cancer metastases because of the lower location of the ovary in the pelvis, less fusion error between PET and CT images, and less interference by respiratory motion during imaging (52)(53)(54). Relevant studies have also demonstrated (27,55) that the diagnostic value of 18 F-FDG PET/CT for suspected epithelial ovarian cancer recurrence is higher than that of conventional imaging examination.…”
mentioning
confidence: 99%